Characterization of avian leukosis virus subgroup J isolated between 1999 and 2013 in China. (19th June 2018) - Li, Jianliang; Meng, Fanfeng; Li, Weihua; Wang, Yixin; Chang, Shuang; Zhao, Peng; Cui, Zhizhong
Abstract: Avian leukosis virus subgroup J (ALV-J ) has successively infected white feather chickens, layer hens, cultivated yellow chickens, and indigenous chickens; infection rates and tumorigenicity have attracted increasingly extensive attention in China. To clarify the correlation of the epidemiological phenomenon of ALV-J with the evolution of envelope protein gp85, 140 strains of ALV-J isolated from chickens with different genetic backgrounds from 1999 to 2013 were compared. The homology of the gp85 protein and genetic genealogical relationships between 140 strains of ALV-J and the prototype strain HPRS-103, as well as between the same ALV-J strains and 8 American isolates, were analyzed and compared. The results showed that there was no significant difference in the variation range of homology of the gp85 protein between the prototype HPRS-103 and ALV-J isolates from different genetic backgrounds and different years. However, genetic pedigree analysis showed that virus strains that isolated from the same type of chickens remained close to each other on the phylogenetic tree, which means that there was a correlation between the genetic background of infected chickens and virus strains. Further analysis of amino acid sequences also found similar results and revealed that unique amino acid sites were formed in chickens with different genetic backgrounds, which proved that ALV-J could adapt to the new host through amino acid variation. Genetic sequence phylogenetic tree analysis was more representative than sequence homology comparisons for assessing ALV-J correlations. These conclusions contributed to the control and prevention of ALV infection. ALV-J is still prevalent in Chinese indigenous chickens, more attentions should be given to fulfill the purification.